Clinical characteristics and visual outcome of Vogt Koyanagi Harada disease patients in a specialized eye hospital in Nepal - Bastola Paudel, Jyoti; Manandhar, Anu; Shrestha, Smita (Journal of Nepal Health Research Council, 2025)
Background: To evaluate clinical characteristics and visual outcome of Vogt-Koyanagi-Harada disease patients in Nepal.Methods: Retrospective series of all the cases of VKH treated at Tilganga Institute of Ophthalmology from 1st July 2017 to 31st June 2022.Results: Fifty-four cases were included, 18(33.33%) were male and 36 (66.67%) were female. Mean age was 41.47±15.57 years and median age was 38 years. All cases were bilateral. Two patients had a complete presentation (3.7%), thirty an incomplete presentation (55.5%) and twenty-two had a possible syndrome (40.7%). Fortysix (85. 1%) patients presented at acute uveitic stage and eight (14.8%) presented at chronic recurrent stage. The most common extraocular finding in our patient population was headache (59.2%). Posterior segment findings included exudative retinal detachment in 40(74%), disc edema in 33(61.1%) and sunset glow fundus in 3(5.5%).Conclusions: Bilateral panuveitis is the most common ocular manifestation of VKH and majority of eyes present with exudative retinal detachment. Oral prednisone with or without immunomodulatory therapy was the primary treatment.Keywords: Immunomodulatory therapy; Nepal: panuveitis; vogt-koyanagi-harada disease.